(untitled) (Conferencea, 2022)
In this article, the history of the origin of makom art, the stages of the development of makom art in the society of individuals, the famous musician and scientist Darvish Ali Changi, who lived in the second half of the 16th century and the first quarter of the 17th century, were written in the treatise “Tuhfat us-surur” “Navruzi Ajam”, “Navruzi Horo”, “Navrozi Sabo” status works are given